Agile-Omoluabi Leadership, Technology-Transfer, Government Willingness to Change, Engagement and Organizational Citizenship Behavior: Examining the Moderating-Mediating Role of Workplace Happiness in Nigeria’s Healthcare System - Onamusi Abiodun Babatunde; Olukolu Yetunde Magret (International Journal of Engineering and Management Research, 2023)
On the backdrop of the aggressive move by the healthcare workers in Nigeria to foreign countries to ply their expertise, the country has suffered her worst brain-drain episode leading to been labelled among the 55 countries experiencing healthcare short in Africa. This is right and it call for an array of contextual issues including; leadership, technology transfer, government willingness to change, engagement, organisation citizen behaviour and workplace happiness to tackle this rather unfortunate incidence. A validated questionnaire was employed to gather data from 408 health-care practitioners including doctors, nurses, pharmacists, technologists and administrators in public-owned hospitals in Nigeria. A path analysis was used to examine the six-way direct, mediation, and moderation hypotheses. Results showed that agile-Omoluabi leadership, government willingness to change and technology transfer had positive and significant effect on engagement (Adj R2 =0.685, p=0.000, Q2 =0.484), workplace happiness stood as a positive and significant intervening variable mediating the interaction between agile-Omoluabi leadership and organisation citizen behaviour (β=0.257, t= 2.033, p= 0.043) as well as serving a moderator for the linkage between engagement and organisation citizen behaviour (β =0.300; p< 0.000, Q2 =0.365). The findings of this study as practical implication for the ministry of health in Nigeria because it offers strategic information which confirms the twofold relevance of workplace happiness as critical to sustaining health-care practitioners’ engagement and guaranty exhibiting citizen behaviour. Also reinforce the need for government at all levels to show readiness to transform, plan and implement a systematic process of technology transfer and show a leadership that care about the health-care practitioners and one that is dynamic. This if done, should address the brain drain and improve the lost glory of the health-care system in Nigeria.